Comparison of Effectiveness of Intra-articular Corticosteroid Injection and Splinting in the Treatment of Rhizarthrosis - Münevver Fatma Şaşmaz; Göknur Karahan; Canan Çelik (Archives of Rheumatology, 2007)
Objective: This study aims to compare the effectiveness of intra-articular corticosteroid injection and splinting on pain and hand function in the treatment of rhizarthrosis. Patients and Methods: Thirty patients diagnosed with rhizarthrosis were included in this study. The patients were randomly divided into two equal groups. An injection of a single intra-articular corticosteroid was made into the 1. carpometacarpal joint (CMC) of the patients of the first group. A wrist spica splint supporting the thumb was given to the patients of the second group. The study covered a 6 week period. The hand joints protection programme was taught to both groups. The patients of both groups were evaluated at the beginning and at the end of the third and sixth weeks. The parameters used to evaluate the patients include the following; visual analog scale (VAS), the number of swollen and painful joints, range of motion (ROM), grip strength, pinch strength and Duruöz hand scale. Eleven patients were eliminated from the study due to their absence at the control evaluations, thus the study was completed with nineteen patients. Results: The study revealed no significant differences (p>0.05) among the two groups in terms of age, gender, body mass index, suffering period and affected side. The study also pointed out that patients in both injection and splint treatment groups exhibited lowered pain, decreased VAS values (relaxed, in motion and with pressure) without statistical difference to each other (p >0.05). Although evaluations at the beginning, third week and sixth week resulted in no significant differences in the number of swollen and painful joints, ranges of flexion, extension and adduction of 1. CMC joint, grip and pinch strength in both groups (p>0.05), there was significant improvement on the abduction ROM and Duruöz hand scale (p=0.006 and p=0.002 respectively) in the injection group. But no significant difference was found between significant difference between corticosteroid injection and splint treatment groups about all parameters. Conclusion: In the treatment of rhizarthrosis, it is considered that there is no difference between an intra-articular corticosteroid injection and splinting, but in the injection group, there is significant improvement in the abduction ROM and functional status. (Rheumatism 2007; 22: 1-5)